Health Matters - Coasters Association (2007)
Number of pages: 20

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2007)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

YES E-News : September 2007 - Youth Employment Services (YES) (2007)
Number of pages: 1

YES Montreal Presents the Meet the Experts Seminar Series : Focus on the Growing Trends in Green Businesses and Social Entrepreneurship - Youth Employment Services (YES) (2007)

Health Matters - Coasters Association (2007)
Number of pages: 12

ELAN Speech to Parliamentary Committee on CBC Review - English Language Arts Network (ELAN) (2007)

Discussion Document #1 : Demographics and the Long-term Development of the English-speaking Communities of the Greater Montreal Region - Quebec Community Groups Network (QCGN); Greater Montreal Community Development Initiative (GMCDI) (2007)

Creating Sustainable Initiatives to Retain and Maintain Health and Social Services Professionals on the Lower North Shore - Lavallée, Marissa (Coasters Association, 2007)
The Coasters Association, in partnership with the Centre de Sant et de Services Sociaux de la Basse-C te-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University, for seven weeks from February 13th to March 31st, 2006, Phase 1, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining English Professionals on the Lower North Shore. The objective of this needs assessment was to develop Phase II which is a two-year proposal that would lead to the improvement of hiring and retaining Health and Social Services Professionals on the Lower North Shore. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the territory. Another objective of this needs assessment is to contact institutional and community-based objectives (i.e Education & Health and Social Services) it is hoped that these contacts will lead to partnerships that will help to address the hiring and retention of English-speaking Professionals on the Lower North Shore.
Parallel title: Measure 2 : Retention and Distance Professional and Community Support Program November 6 2006 to March 31 2007

The 10th Anniversary YES Entrepreneurship Conference : March 3/2007 - Youth Employment Services (YES) (2007)

Food Transportation Consultation - Coasters Association (2007)
Parallel title : A Portrait of the Food Industry Relating to Residents of the Lower North Shore

Dialogue : Better Communication for Better Care - Dialogue McGill (2007)
issued: Spring, 2007/Summer, 2007 Number of pages: 7

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2007)
issued: Spring, 2007/Summer, 2007 Number of pages: 5

Report of the Greater Montreal Community Development Initiative Steering Committee : Building Upon Change and Diversity within the English-speaking Communities of the Greater Montreal Region: - Greater Montreal Community Development Initiative (GMCDI) (Quebec Community Groups Network (QCGN), 2007)
In the 30 years since the passage of Bill 101, the nature of the English-speaking communities of the Greater Montreal Area has changed dramatically. The evolution of the largest linguistic minority within a linguistic minority in Canada has resulted in the emergence of certain unique challenges and opportunities. It was to address these issues that the Greater Montreal Community Development Initiative (GMCDI) was launched. This initiative, funded by the Department of Canadian Heritage, is intended to assist the English-speaking communities of the Greater Montreal Area in identifying shared community development challenges and priorities, and the most effective strategies to address them.
Keywords: Official Language Minority Community (OLMC)

Special Needs Project - Lavallée, Marissa (2007)

Program Book: Winter / Spring 2007 - Youth Employment Services (YES) (2007)